The Bidirectional Relationship between Positive Mental Health and Social Rhythm in College Students:A Three-Year Longitudinal Study - Cai, Dan; Zhu, Meixia; Lin, Muyu; Zhang, Xiao Chi; Margraf, Jürgen (Frontiers in Psychology, 2017)
Social rhythm refers to the general regularity of engaging in basic social activities during the week, and was found to be associated with individuals' positive mental health. The present study investigated the relationship between social rhythm and emotional well-being in a cohort of 2,031 college students over three years with a cross-lagged longitudinal panel design. Results revealed that regularity of social rhythm positively predicted emotional well-being in the following year, and vice versa, when the level of both factors in the previous year was controlled. Our study provides evidence of a longitudinal positive reciprocal relationship between social rhythm and positive mental health in younger adult populations.